A new model path for the development of smart leisure sports tourism industry based on 5G technology. Issue 5 (8th September 2021) - Liang, Feng; Mu, Lili; Wang, Dongle; Kim, Byung‐Sik
Abstract: In recent years, national and local governments have attached great importance to the development of tourism big data, and have proposed an active development of the 'Internet + Tourism' strategy to cultivate new forms of tourism in various forms. With the development of 5G technology, the tourism industry also needs to study new development paths. The traditional tourism industry cannot obtain relevant information of tourists on time, nor can it provide satisfactory services, which has brought troubles to the traditional tourism industry. However, with the support of 5G technology, smart tourism is increasingly meeting the needs of the public and improving the level of tourism services. Based on this, this paper proposes a new model path research for the development of the smart leisure sports tourism industry based on 5G technology. This paper adopts the literature method to learn the theoretical basis of 5G technology and smart tourism in depth; through 5G technology, establishes a multi‐dimensional resource allocation model for the smart leisure sports tourism industry, and conducts research on the influencing factors, information sources, channel factors and other aspects of the tourism industry. The general public's search for tourism strategies and attractions, food and specialty products, the use of online search information channels accounted for 70.3% and 69.3%, which further shows that the development of 5G technology has promoted the transformation and development of the sports tourism industry.